Linking actual self-congruence, ideal self-congruence, and functional congruence to donor loyalty: the moderating role of issue involvement - Adnan Zogaj; Dieter K. Tscheulin; Jörg Lindenmeier; Stephan Olk (Journal of Business Economics, 2020)
Nonprofit organizations need loyal donors to accomplish their mission and goals. However, organizations lose up to 60% of their first-time donors. Therefore, a deeper understanding of the determinants of donor loyalty is necessary. This study tests whether actual self-congruence, ideal self-congruence, and functional congruence strengthen the tie between nonprofit organizations and donors. In addition, and as an extension of the self-congruence theory, issue involvement is added as a moderator variable. The study results show that ideal self-congruence and functional congruence have a positive effect on donor loyalty, while actual self-congruence does not affect donor loyalty. Moreover, the study results show that issue involvement strengthens (mitigates) the effect of actual self-congruence (ideal self-congruence) on donor loyalty. Regarding the relationship between functional congruence and donor loyalty, issue involvement has no moderating effect. Based on the empirical findings, this study discusses academic implications and presents managerial implications for fundraisers and nonprofit organizations.
Keywords: M31; M37; 650; Actual self-congruence; Ideal self-congruence; Functional congruence; Donor loyalty; Issue involvement